2018
DOI: 10.1111/1460-6984.12373
|View full text |Cite
|
Sign up to set email alerts
|

Writing fluency in patients with low‐grade glioma before and after surgery

Abstract: BackgroundLow‐grade glioma (LGG) is a type of brain tumour often situated in or near areas involved in language, sensory or motor functions. Depending on localization and tumour characteristics, language or cognitive impairments due to tumour growth and/or surgical resection are obvious risks. One task that may be at risk is writing, both because it requires intact language and memory function and because it is a very complex and cognitively demanding task. The most commonly reported language deficit in LGG pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The identified studies found wide variability in the reported effects of tumor-related factors on cognitive outcomes in patients with gliomas. Anatomical location of the tumor has been shown to be an important influence on cognitive outcomes in some studies ( 23 35 ), but not in others ( 3 , 36 40 ); although most of the studies providing evidence for and against a role of anatomical location were prospective cohort studies (some study designs in both groups were not specified), the studies suggesting no role of anatomical location were fewer and tended to have smaller numbers of participants, and on balance anatomical location is most likely to be relevant overall for cognitive function. Location of the tumor has been shown to influence the likelihood of developing deficits in some but not all cognitive domains ( 41 ), and in another study was found to predict spontaneous speech deficits and naming scores in HGG but not LGG patients ( 42 ); the authors of the latter study hypothesize that this implies that large functional reorganization occurs in LGG, and highlights the importance of glioma grade in macrostructural plasticity mechanisms that modulate brain-behavior relationships.…”
Section: Resultsmentioning
confidence: 99%
“…The identified studies found wide variability in the reported effects of tumor-related factors on cognitive outcomes in patients with gliomas. Anatomical location of the tumor has been shown to be an important influence on cognitive outcomes in some studies ( 23 35 ), but not in others ( 3 , 36 40 ); although most of the studies providing evidence for and against a role of anatomical location were prospective cohort studies (some study designs in both groups were not specified), the studies suggesting no role of anatomical location were fewer and tended to have smaller numbers of participants, and on balance anatomical location is most likely to be relevant overall for cognitive function. Location of the tumor has been shown to influence the likelihood of developing deficits in some but not all cognitive domains ( 41 ), and in another study was found to predict spontaneous speech deficits and naming scores in HGG but not LGG patients ( 42 ); the authors of the latter study hypothesize that this implies that large functional reorganization occurs in LGG, and highlights the importance of glioma grade in macrostructural plasticity mechanisms that modulate brain-behavior relationships.…”
Section: Resultsmentioning
confidence: 99%
“…The logging program appears as a plain word processor with a document in which the writers produce their texts. Keystroke logging has been used for a variety of purposes, including to analyse the writing of dyslexic students (Wengelin, 2002), persons with brain tumours (Antonsson et al ., 2018), persons with Alzheimer's disease (Van Waes et al ., 2017) and persons with post‐stroke aphasia (Behrns et al ., 2008, 2009a; Johansson‐Malmeling et al ., 2021a,b). In the present study, the logging tool was used for all written tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, other studies have taken a more active look at the role of language in texts composed on a computer, and have moved into areas such as the frequencies with which parts of speech occur (Behrns et al, 2008(Behrns et al, , 2010Wengelin, 2007), pause lengths between language units as indicators of language impairment (Antonsson et al, 2018;Van Waes et al, 2017), and how writers consult and use sources (Leijten et al, 2019). However, there is little research into how language (or meaning) unfolds in written text (cf.…”
Section: The Role Of Revision In the Writing Processmentioning
confidence: 99%